Cerdota grandota - Blackstone, Stella; Beaton, Clare; Canetti, Yanitzia, 1967- (Cambridge, MA : Barefoot Books, 2006)
Contrasts animals in the barnyard, including clean and dirty geese, fat and thin cows, and big and small pigs.
Keywords: English language -- Synonyms and antonyms -- Juvenile fiction; Domestic animals -- Juvenile fiction; Stories in rhyme -- Juvenile fiction; Animales domésticos -- Novela juvenil; Cuentos en rima -- Literatura juvenil